Minimizing the opportunity cost of Excel Coil Coating Corporation using moving average forecasting technique - Agapito, Jude Vito C.; Encarnacion, Carlitos P. III; Monreal, Mark Emil G. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
This study centers on the opportunity cost of Excel Coil Coating Corporation on its nine gauges of galvanized iron sheets. With the information currently given by the management, the group was able to note that the company used intuition and past experiences in determining the number of metric tons of galvanized iron sheets to be ordered. Additional investigation of the company process and interviews with the management noted that a new marketing strategy was implemented during the year of 2015; thus, all data points from 2013 to 2014 were deemed inappropriate for the study. In addition to these, company policies such as minimization of shortages, allowance of excess supply in inventory, and an average opportunity cost of Php 5,000 per metric ton led to the group's goal of minimizing opportunity cost of the company from Php 9,375,000 to the tolerable amount of Php 3,000,000 for the fourth quarter of 2015 to the first quarter of 2016. The group applied a combination of moving averages with periods equal to N=2 and N=3 and presented a table showing the comparison and computation of opportunity cost of determine the period value "N" that will incur the smallest cost per product. Results showed that from Php 9,375,000, the group was able to lower the opportunity cost to Php 3,208,333. In addition to this, since the start of a new marketing strategy is equivalent to a new beginning for possible demand patterns, the group also recommended that the company monitors future demand patterns with the simple scenario analysis.
Submitted in partial fulfillment of the course requirements in IE 151 : Production systems.
Keywords: Iron, Galvanized; Business forecasting; Opportunity costs; Moving average; Scenario analysis